The Growth of Fintech on Student Loan Products in Indonesia: A Literature Study - Farida; Dhieka Avrilia Lantana; Kumba Digdowiseiso; Rohana Ahmad (CV ODIS, 2023)
Forming a person's intellect and character can be done through a qualified education system. An effective medium for formation is through education. However, in reality in Indonesia education is still not evenly distributed, both in terms of quality and quantity. Therefore, student loans through fintech are here to facilitate a person's accessibility to education. However, the development of fintech in Indonesia has not yet been studied in depth, so the aim of this research is to examine the growth of student loans in fintech in Indonesia. The method used is based on a literature study with qualitative descriptive data analysis. The findings show that the growth of fintech in student loan products in Indonesia is quite significant. This growth was driven by several certain factors in both COVID-19 and normal conditions. The Covid-19 phenomenon is driving digital technology transformation to become increasingly massive, while under normal conditions business motives, technological developments, increasing tuition fees, and diverse student backgrounds also encourage the growth of student loans in fintech in Indonesia